Gingival Rebound and Healing Following Gingivectomy Using Diode Laser and Conventional Surgery: A Prospective Observational Comparative Study - Shibu Periera; Bindu Nayar; Rekha Radhakrishnan; Lekshmi Jayasree; Susanna Brainerd (International Journal of Scientific Research in Dental and Medical Sciences)
Background and aim: The healing process after Gingivectomy can vary depending on the technique used, with both diode laser and conventional scalpel methods providing satisfactory results but differing regarding postoperative recovery. Coronal displacement of the gingival margin is a possible and unwanted sequel of the gingivectomy procedure. This study aims to compare the laser and scalpel gingivectomy and determine differences in tissue rebound, healing, postoperative pain, and the need for analgesics post-gingivectomy in these patients. Material and methods: Thirty-two patients were consecutively recruited into the two groups. The parameters evaluated included pain perceived postoperatively after 30 minutes on the 7th and  14th Day, healing on the 7th, 14th, and  30th Day, gingival tissue rebound on the 14th  and  30th Day, and analgesics required in the postoperative period. Results: There was a significant difference in gingival index and gingival relapse on the 14th Day and  30th Day between the groups, with a lesser amount of relapse in the laser group. Groups I and II showed statistically significant differences in healing, with the scalpel group recording better healing in all follow-up appointments. There was no significant difference in pain scores and postoperative analgesic intake. Conclusions: The study demonstrated that coronal displacement of the gingival margin was comparatively lesser in the laser group, even though it had delayed healing. Combining both techniques might enhance clinical outcomes, particularly in managing gingival inflammation and migration in the initial months following surgery.